Pan-cancer analysis reveals distinct clinical, genomic, and immunological features of the LILRB immune checkpoint family in acute myeloid leukemia - Zi-jun Xu; Xin-long Zhang; Ye Jin; Shi-sen Wang; Yu Gu; Ji-chun Ma; Xiang-mei Wen; Jia-yan Leng; Zhen-wei Mao; Jiang Lin; Jun Qian (Molecular Therapy: Oncolytics, 2022)
Leukocyte immunoglobulin (Ig)-like receptor Bs (LILRBs), a family of type I transmembrane glycoproteins, are known to inhibit immune activation. Here, we comprehensively evaluated the molecular, prognostic, and immunological characteristics of LILRB members in a broad spectrum of cancer types, focusing on their roles in acute myeloid leukemia (AML). We showed that LILRBs were significantly dysregulated in a number of cancers and were associated with immune-inhibitory phenotypes. Clinically, high expression of LILRB1-LILRB4 predicted poor survival in six independent AML cohorts. Genetically, LILRB1 was associated with more mutational events than other LILRB members, and multiple genes involved in immune activation were deleted in LILRB1high patients. Epigenetically, LILRB4 was significantly hypomethylated and marked by MLL-associated histone modifications in AML. Immunologically, LILRBs were positively associated with monocytic cells, including M2 macrophages, but were negatively associated with tumor-suppressive CD8 T cells. Importantly, patients with higher LILRB expression generally showed a better response to immune checkpoint blockade (ICB) in five independent immunotherapy cohorts. Our findings reveal critical immunological and clinical implications of LILRBs in AML and indicate that LILRBs may represent promising targets for immunotherapy of AML.